Nanofat, Microfat, Platelet Rich Plasma (PRP), Microneedling and Fractional CO2 Laser: A Regenerative Multimodality Approach and Protocol in Scar Management - Mandili, Aeshah; Alsadi, Hazim Hamed S; Khamis, Sherif; Alharbi, Ziyad (Archives of Clinical and Medical Case Reports, 2022)
Background: Scars are the natural end-result of healing process following skin injury that extends to the reticular dermis. Recently, a worldwide effort was undertaken to investigate the regenerative potential of adipose tissue grafting, platelet rich plasma, and microneedling technique. Only few studies have shown its effect on scars. It is hypothesized that the Adipose-Derived Stem Cells (ADSCs) and numerous growth factors contained in the lipoaspirate as well as in the Platelet Rich Plasma (PRP) that contribute to the skin and scar remodeling. The purpose of this study was to evaluate the clinical regenerative effect of using combined well-arranged different collaborative modalities including: autologous microfat, nanofat graft, platelet rich plasma and microneedling followed by fractional CO2 laser on scars. Methods: This is retrospective analysis that was conducted in KAMC, Saudi Arabia by the same surgeon. Overall, eight patients were treated using autologous microfat, nanofat graft, then three sittings of PRP with microneedling technique treating the scars, followed by session of fractional CO2 Laser. Evaluation was based on physician clinical assessment reflecting significant improvement exactly three months post-treatment. Results: All eight patients had significant improvement of scar appearance with good satisfactory outcome regarding the quality of scars. Conclusion: This case series has demonstrated the potential safety and efficacy of the combination therapy of autologous microfat, nanofat graft, platelet rich plasma, microneedling and fractional laser for the treatment of scars.